PENGARUH JENIS STEK DAN KONSENTRASI ZAT PENGATUR TUMBUH GROWTONE TERHADAP PERTUMBUHAN TANAMAN NILAM (Pogestemon cablin Benth) - Rusdi Faizin (Universitas Teuku Umar, 2018)
This study aims to determine the effect of type of cuttings and concentration of growth regulators on the growth of plants Growtone patchouli and real absence of the interaction of both factors.This research was conducted at the Experimental Farm at the University of Teuku Umar Meurebo District of West Aceh district. Research began on August 3 until September 3, 2015. The material to be used in this study is a cuttings patchouli with age and the same diameter, the upper soil (top soil), in the form of cow dung manure is ripe, grow roots aphrodisiac brands Grow Tone and fungicide Dithane 46. The tools used in this study is polybag, 30 cm wooden ruler, paranet 50% of light, gembor. Signboard and treatment license plate and stationary for supporting the research.The experimental design used in this study was a randomized block design (RAK) 3 x 4 factorial design with three replications. Factor Type Cuttings consists of three levels ie: S1 = cuttings shoots; S2 = cuttings limb; S3 = stem cuttings. PGR concentration factor (Z) used consists of three levels, namely: Z0 = 0 g ml-1 water; Z1 = 3 g ml-1 water; Z2 = 6 g ml-1 water; Z3 = 9 g ml-1 of water.The results showed that the type of cuttings significant effect on the number of leaves of patchouli at the age of 14, 28, 42 and 56 days after planting (DAP), shoot length at the age of 42 and 56 (HST), the number of roots and root length at the age of 56 HST, Real impact on the long shoots at the age of 14 and 28 days after planting. No real effect on percentage of cuttings life at the age of 56 HST. Of the various types of cuttings were tested patchouli, patchouli plant growth best in the encounter on the type of patchouli shoot cuttings (S1).The results of the research that has been conducted shows that the dose concentration Growtone very significant effect on the number of leaves of patchouli at theage of 14, 28, 42 and 56 days after planting (DAP), shoot length at the age of 42 and 56 (HST), the number of roots and root length at the age of 56 HST. Real impact on the long shoots at the age of 14 and 28 days after planting. No real effect on percentage of cuttings life at the age of 56 HST. Of various concentrations of plant growth is tested growtone the best value found in the treatment with a concentration of 6 g cuttings growtone-1 (Z2). There is no real interaction between treatment type and concentration Growtone cuttings of all the observed variables. Keywords: cuttings type, patchouli, plant growth, ZPT Growtone